The future of work: an empirical examination of job perception of gig workers - Hiramoto, Rogerio Kiyoshi (2019)
The advancement of information technologies is driving the future of work and it is enabling new employment conditions worldwide like gig work, which will be 50% of the American working population by 2050. The workers are seeking flexibility, autonomy, and empowerment that could be achieved thru the gig work. This paper exanimates 351 users from MTURK (Amazon Mechanical Turk) platform from The United States of America and India. The conclusions show that gender and the educational level does not impact their income, however Experienced Users and those who started their career directly in the platform tend to have a higher income.